Fresh-cut watermelon: postharvest physiology, technology, and opportunities for quality improvement - Quandoh, Ebenezer; Albornoz, Karin (Frontiers in Genetics, 2025)
Watermelon (Citrullus lanatus L.) fruit is widely consumed for its sweetness, flavor, nutrition and health-promoting properties. It is commonly commercialized in fresh-cut format, satisfying consumer demand for freshness and convenience, but its shelf-life is limited. Despite the potential for growth in fresh-cut watermelon sales, the industry faces the challenge of maintaining quality attributes during storage. Fresh-cut processing induces a series of physiological and biochemical events that lead to alterations in sensory, nutritional and microbiological quality. A signal transduction cascade involving increases in respiration and ethylene production rates and elevated activities of cell wall and membrane-degrading enzymes compromise cellular and tissue integrity. These responses contribute to the development of quality defects like juice leakage, firmness loss and water-soaked appearance. They also drive the loss of bioactive compounds like lycopene, affecting flesh color and reducing nutritional value, ultimately culminating in consumer rejection, food losses and waste. Although great research progress has been achieved in the past decades, knowledge gaps about the physiological, biochemical and molecular bases of quality loss persist. This review article summarizes the advances in the study of physicochemical, microbiological, nutritional, and sensory changes linked to the deterioration of watermelon after processing and during storage. Different technological approaches for quality improvement and shelf-life extension are summarized: pre- and postharvest, physical, and chemical. We also discuss the advantages, disadvantages and challenges of these interventions and propose alternative directions for future research aiming to reduce qualitative and quantitative fresh-cut watermelon losses.